Application of Laclau and Mouffe's Discourse Analysis Methodology in Political Science - Nasrallah Hejazi; vahid bahrami (روش شناسی علوم انسانی, 2019)
One of the qualitative methods that political science scholars interest in examining its concepts and developments is the Laclau and Mouffe discourse analysis method. The main question of this research is how to use and apply the method of discourse analysis in the field of political science, and how and to what extent can discourse analysis be used to understand and explain political science? The claim and assumption of this research is possibility of using the knowledge of discourse analysis in various fields of political science is not completely eliminated, the application of the discourse-analysis approach in the field of politics opens up new horizons and yields significant methodological and theoretical results